Synthesis and Characterization Thin Film TiO2 as Degrading Procion Red MX-8B Textile Dye - Almu’minin, Achmad Sholikhudin; Haryati, Tanti; Mulyono, Tri (Jurnal ILMU DASAR, 2016)
TiO2 photocatalyst is one of type semiconductor that is often used in textile dyes photodegradationmethod which characteristics are influenced by the size of crytal. Synthesis of TiO2 photocatalystscan be done by several methods, one using the sol-gel method. By treating variations in thecomposition of the reactans and treatment of synthesis in sol-gel method, the size of the TiO2crystals can be controlled to produced the desired characteristics. This study has been made ofTiO2 photocatalysts in the form of thin-layer films using sol-gel method with annealing process ata temperature of 550oC. This study examines the effect of the concentration of precursor TTIP andhydrolysis ratio of the crystal structure, crystallinity, the band gap energy, and photocatalystactivity to degrade procion red mx-8b dye compound. The result obtained is known that the crystalsynthesized has structure of TiO2 anatase. Value crystal size, crystallinity, the band gap energy,and percent degradation has a value that depends on the composition of TTIP concentration andhydrolysis ratio. Although the results showed morphology of TiO2 particle indivcate that large sizeand crystallinity value is still low, but that is interesting each of the measurement results mutuallysupport each other.Keywords: photocatalyst, TiO2, Sol-gel, TTIP concentration, hydrolysis ratio